The Definition of Specific-Purpose English Language Competences Needed in Border Control and Their Development Potentials: III. English for Border and Coast Guards: Specific-Purpose English Language Skills and the FRONTEX Courses Designed for Their Development – Level B2 - Dr. Borszéki, Judit (Magyar Rendészet, 2021)
The first part of this series of papers discussed the dilemmas and methodology related to the definition of specific-purpose language competences and to needs analyses, crucial for language course design in general and their application in the context of English for Border Guards (EBG) in particular. In the further articles of the series I wish to prove that the ongoing FRONTEX (European Border and Coast Guard Agency) project entitled English Communication for Border and Coast Guards (ECBCG) very well illustrates how the new approach to needs analysis methods, similar to the one showcased in the first part of this series of papers is used to define the English language skills needed for border control in the EU. My other hypothesis is that, based on the authentic material provided by border guards, using the system approach, the English for Specific Purposes (ESP) competences needed for their work can be defined according to the categories generally used in applied linguistics and the Common European Framework of Reference for Languages (CEFR). The second paper discussed the elementary and intermediate (A2/B1) EBG competences, now called ‘Level 1’ in the ECBCG FRONTEX online course. This third part presents the upper-intermediate ones (B2, Level 2).